INTERVAL ESTIMATION OF OBJECT RELIABILITY INDICES - L. I. Kulbak (Informatika)
The paper describes a method of interval estimation of reliability indices of an object having a consistent block diagram of reliability calculation and input data for calculation of reliability indices in the form of interval estimates. The technique is based on the model of indirect measurements.